Drug-Selected Resistance Mutations and Non-B Subtypes in Antiretroviral-Naive Adults with Established Human Immunodeficiency Virus Infection - Hanna, George J.; Balaguera, Henri U.; Freedberg, Kenneth A.; Werner, Barbara G.; Steger Craven, Kathleen A.; Craven, Donald E.; D’Aquila, Richard T. (The Journal of infectious diseases, 2003)
The prevalence of human immunodeficiency virus (HIV) type 1 antiretroviral resistance is expected to be higher in recently infected antiretroviral-naive individuals than in those who have been infected longer. Antiretroviral-naive HIV-1–infected adults who presented to an outpatient clinic in an urban hospital in Boston for initial evaluation in 1999 were screened for drug-selected resistance mutations and phylogenetic subtype. Drug-selected mutations were identified in 16 (18%) of 88 subjects. Twelve (14%) included mutations associated with nucleoside reverse-transcriptase inhibitors, 4 (5%) included mutations associated with nonnucleoside reverse-transcriptase inhibitors, and 3 (3%) included mutations associated with protease inhibitors. Two (2%) had resistance mutations associated with multiple classes of drugs. Nine (10%) subjects had infection with non-B subtype HIV-1 and did not have drug-selected mutations. Serological results indicated infection for ⩾6 months. Drug-selected mutations or non-B subtypes were detected in a substantial portion of antiretroviral-naive adults who had been infected for at least 6 months